Genetic variants and hamstring injury in soccer: An association and validation study - Larruskain, J.; Celorrio, D.; Barrio, I.; Odriozola, A.; Gil, S. M.; Fernandez-Lopez, J. R.; Nozal, R.; Ortuzar, I.; Lekue, J. A.; Aznar, J. M. (Medicine & Science in Sports & Exercise, 2018)
PURPOSE: This study aimed to investigate the association of candidate single nucleotide polymorphisms (SNP) with noncontact hamstring muscle injuries in elite soccer players and to create and validate a model to assess the risk of hamstring injury.